How China and Chinese people are visually represented: The case of a series of Liberal Studies textbooks in Hong Kong - Wu, Yuxi; Li, Yulong (Journal of Education Culture and Society, 2022)
Aim. The aim of the research is to examine how Mainland China and Chinese people are represented in the visual materials of four sets of Liberal Studies (LS) textbooks in Hong Kong. Methods. Fairclough’s Critical Discourse Analysis, viewing language as a social practice and van Dijk’s ideological coding categories are integrated to analyze discursive representations (e.g., the embedded hidden power) in the Hong Kong Today volumes published by four influential commercial publishers: Modern, Ming Pao, Marshall, and Aristo. Results. The analysis reveals that China and mainland Chinese are negatively portrayed in visual images in four commercial LS textbooks, in which, the representations concerning mainland China and mainlanders are all found ideologically biased to highlight their negative characteristics and alienness.Conclusions. Via an overview of Hong Kong’s history, economy, educational policies, and controversial political events, the reasons why China and its people are represented negatively in LS textbooks is explained.